Semantic alignment in museums, archives and libraries. The ontologies for describing relationships - Valentina Carriero; Marilena Daquino; Francesca Tomasi (JLIS.it, 2019)
This paper presents the state of the art of the cataloguing description of personal relationships between creators of archival records and people that are related to the life cycle of cultural objects, as highlighted by museums, archives and libraries records (i.e. GLAM, translated in italian MAB). Since people are fundamental access points to the cultural heritage, the representation of relationships between people and corporate bodies in Linked Open Data is of increasing interest. Nonetheless, a shared and comprehensive vocabulary of personal relationships is not available yet. Leveraging on Semantic Web technologies, and ontologies in particular, the aim is to identify existing ontologies that allow to represent relationships in their context (i.e. time, space and events); to map and classify different types of personal relationships; and to provide a formal representation of relationships not available in existing ontologies. As a result, we present an ontology, with a controlled vocabulary, for the representation of the scenario of personal relationships in the cultural heritage domain.